A 200 GHz Subharmonic Resistive Mixer and an IF Amplifier Based on GFETs - Zhang, Yaxin (My University, 2016)
In recent years, graphene, a two-dimensional monolayer of carbon atoms, has rapidly attracted great attention in high-speed electronics. The promising property such as the high intrinsic carrier mobility as well as high carrier saturation velocity make graphene a potential candidate for high-speed transistors operating in the millimeter wave and the terahertz frequency ranges. In this thesis, a 200 GHz subharmonic resistive mixer and a microwave amplifier based on graphene FET (GFET) are presented. The mixer is designed to down convert 200 GHz to 1 GHz with LO frequency of 100.5 GHz, and the amplifier is operating at 1 GHz. A large-signal GFET model is set up in a standard circuit simulator for the mixer and amplifier device optimisation as well as circuit-device integrative simulation. The device of the amplifier has a gate length 1 μm and a width 2 x 120 μm, and the mixer GFET is designed as Lg · Wg = 0.5 · 80 μm2. An array of bow-tie structured graphene nanoconstructions is applied in the mixer GFET channel to obtain simultaneously a right impedance level as well as a higher current on-off ratio. Chemical vapor deposition (CVD) method is utilised for graphene preparation, and the mixer and amplifier circuit are realised in coplanar waveguide (CPW) technology on a 100 μm thick high resistive silicon substrate. A planar inductor is applied in the amplifier design for the purpose of input matching as well as circuit’s integration. Metal air-bridges are added in final layout for reducing circuit discontinuities and parasitic mode propagation at the circuit T junction. Full-wave EM simulations are used for the passive circuits design. The first version of integrated receiver circuit including the designed mixer and amplifier is also fabricated. The conversion loss (CL) of the mixer over the RF frequencies from 190 to 210 GHz is measured to be 34 dB ± 3 dB, with the minimum CL of 31.5 dB at 190 GHz and 10 dBm LO pump power. The amplifier power gain is measured to be 6 dB at 1 GHz.
Keywords: Informations- och kommunikationsteknik; Nanovetenskap och nanoteknik; Elektronik; Elektrofysik; Information & Communication Technology; Nanoscience & Nanotechnology; Electronics; Electrophysics